Solid Dispersion of Tenoxicam – HPMC by Freeze-Drying: Solid State Properties, Dissolution Study, and Analgesic Activity in Mice - Umar, Salman; Usman, Hendrizal; Salsabila, Hulwa; Zaini, Erizal (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: The aim of this study was to prepare solid dispersion of tenoxicam with hydroxypropyl methylcellulose (HPMC) to improve solubility, dissolution rate, and in vivo analgesic activity. METHODS: Solid dispersion of tenoxicam with HPMC was prepared using the freeze-drying technique in three ratios of drug to carrier (1:1, 1:2, and 2:1 w/w). The s olid-state properties of solid dispersion powders were characterized by powder X-ray diffraction (PXRD), differential scanning calorimetry (DSC), Fourier-transform infrared (FT-IR) spectroscopy, and scanning electron microscope (SEM). Solubility and dissolution rate studies were conducted in an aqueous medium. Analgesic activity was evaluated using the writhing method. RESULTS: Analysis of PXRD and DSC results indicated a decreased degree of crystallinity of tenoxicam in solid dispersion powders. Solid dispersion of tenoxicam exhibited a significant improvement in solubility and dissolution rate compared to intact tenoxicam, in line to the increment on the ratio of HPMC. Analgesic activity study revealed that solid dispersion 1:2 was more effective than intact tenoxicam. CONCLUSIONS: This study concludes that the solid dispersion technique is a promising strategy to improve the solubility and dissolution rate of tenoxicam.